Diagnosing students’ difficulties and strategies to overcome them in physics learning - Muh Asriadi AM; Epi Purnama; Anna Isabela Sanam (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
Diagnosing students' abilities in learning physics is crucial so that learning designs can be tailored to students' actual learning conditions. This study aims to diagnose students' abilities in physics and identify appropriate learning strategies used by physics teachers according to students' needs. The study employed a mixed-methods approach, involving 163 students and five physics teachers from five high schools in Indonesia. The research instruments consisted of a two-tier, 15-item multiple-choice test administered via Microsoft Forms and a semi-structured interview guide for physics teachers. Quantitative data were analyzed descriptively using statistical categorization, while qualitative data were thematically analyzed to identify relevant learning strategies. The diagnostic results indicated that students' abilities in critical thinking, problem-solving, and scientific literacy were in the moderate category, while their conceptual understanding and numerical abilities were in the low category. Furthermore, most students experienced false-negative errors, indicating that they understood physics material conceptually but had difficulty applying those concepts to solve contextual problems. These findings suggest that students' learning difficulties stem from challenges in transferring conceptual knowledge into problem-solving situations. Therefore, teachers are encouraged to implement problem-based learning strategies that guide students in constructing their knowledge through scientific inquiry to find solutions based on accurate physics concepts.